Энергосберегающая технология на предприятиях черной металлургии: [монография] - Егоричев А. П. Александр Павлович; Рудницкий Я. Н. Яков Наумович; Толочко А. И. Алексей Иванович; Филипьев О. В. Олег Владимирович (Харьков, Вища школа, 1986)
Авт. указаны на обороте тит. л.